Pembuatan Peta Tematik Menggunakan Sistem Informasi Geografis (SIG) Pada Desa Teluk Latak - Randhi Saily; Harnedi Maizir; Desi Yasri (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2021)
A strategy from the Bengkalis Government in the context of accelerating regional development and improving the wheels of the economy, regional expansion is carried out both on the sub-district, sub-district and village scales. Teluk Latak Village is one of the villages affected by the expansion so that the distribution of the area or village boundaries becomes invalid. This incident caused confusion in the fields of population, agriculture or plantations, and so on. The purpose of this research is to obtain accurate data and to process the data into a thematic map of the village, so that it can provide information about the situation of the village. The method used is exploratory-survey with the acquisition of measurement data in the field and processed using the Arc-GIS application. The data source is based on taking coordinates using GPS tools and aerial photos using drones. Results that can be displayed on a thematic map of Teluk Latak Village Kab. Bengkalis consists of five information, namely the plantation area is displayed with an area of 1015,141 ha, and a residential area with an area of 132,88 ha. Fishery area with an area of 33.44 ha. Then the road network consisting of arterial roads, neighborhood roads and alleys. Furthermore, the river network serves three other villages, namely Senderak Village, Meskom Village and Simpang Ayam Village.